Optimasi Kecerdasan Kontekstual dalam Multiplikasi Kepemimpinan di Era Digital Pascapandemi (Jurnal Pendidikan Agama dan Teologi, 2025)
Digital era has brought about the widest and unprecedented generational gap between parents and senior leaders on the one side and the next generation on the other. Raising and, more importantly, multiplying leaders in this era requires contextual intelligence. Seniors must apply this crucial intelligent skill in choosing their content, in the way they communicate and in how they form communities. In post-pandemic era, its urgency only increases, hence needs optimizing.